Repeatability of Boldness and Aggression in the Zebrafish and the Guppy (Global Journal of Science Frontier Research, 2017)
Recent studies suggest that personality traits that were previously thought to be plastic may be repeatable within individuals in a population. Repeatability measures how consistent personality traits are.In this study we tested whether boldness and aggression were repeatable in both sexes of three strains of zebrafish(London Wild Type (LWT), Tupfel Long fin (TL) and Nacre) and one population of guppies. Boldness and aggression were highly repeatable in both sexes of the three zebrafish strains, and boldness (not aggression) was repeatable in the population of guppies. The high repeatability estimates in the zebrafish trials suggested that the traits were potentially heritable.
Keywords: personality traits; boldness; aggression; repeatability; zebrafish; guppies